Accountability of Public Institutions: A Bibliographic Survey - Ganeshalingam, K.T.; Fathima Sajeetha, T. (Faculty of Arts and Culture, South Eastern University of Sri Lanka, 2020)
This study is about accountability of public institutions. Accountability is an important aspect of good governance as without it there can be no democratic governance. The purpose of this study is to review the literature available about accountability and identify the gap in previous studies. This study, before focusing on accountability, first searched for the available literature on this topic. Once this was done, theoretical and empirical literature were reviewed. Published books, previous research papers, and the Internet were the secondary sources used to obtain the qualitative data for this study. These secondary sources were analyzed using the descriptive method. Through this study, much knowledge was gained of the actors and processes of accountability, history of accountability, accountability framework, importance of accountability, and types of accountability, by reviewing the theoretical literature. Further, the accountability practices of different countries were scrutinized by going through the empirical literature. An important research gap this study noted was that socio-demographic and administrative factors were not fully identified in previous studies. This gap must be narrowed or eliminated if further progress is to be made in future studies.
Keywords: Accountability; Accountability framework; Responsibility; Transparency